Effect of Raw Material Composition on the Characteristics of Rambusa-Sappan Beverage as a Functional Food Drink - Jenri Parlinggoman Hutasoit; Krisensia Liana Avenesya; Muhammad Liana Fajri; Kharismayati Kharismayati (Journal of Agritechnology and Food Processing, 2025)
Herbal teas derived from local plant resources have considerable potential for development as functional beverages; however, their physical characteristics are strongly influenced by raw material composition. This study aimed to evaluate the effect of the proportion of rambusa leaves and sappan wood on the physical characteristics of rambusa-sappan herbal tea. A completely randomized design was applied with six sappan:rambusa ratios (0:100, 10:90, 20:80, 30:70, 40:60, and 50:50) and three replications. The analyzed parameters included moisture content, water absorption capacity, solubility percentage, pH, and color characteristics (L*, a*, b*). The results showed that formulation significantly affected all evaluated physical parameters. Increasing the proportion of rambusa tended to enhance water absorption capacity and produced a lighter infusion color, whereas higher sappan proportions increased solubility and red color intensity due to the presence of water-soluble pigments and phenolic compounds. All samples exhibited low moisture content and neutral to slightly acidic pH, supporting product stability during storage. The interaction between leaf-based and wood-based materials governed the rehydration behavior and visual characteristics of rambusa-sappan herbal tea in a complementary manner. Overall, rambusa-sappan formulation plays an important role in determining physical quality and visual appearance and can serve as a basis for developing functional beverages from local plant resources with controllable characteristics.